Akibat Hukum Kawin Lari Berdasarkan Hukum Islam Dan UU Perkawinan (Studi Kasus Kec. Tolinggula) - Kaunang, Alfian; Dungga, Wenny Almoravid; Bakung, Dolot Alhasni (CV. ITTC INDONESIA, 2022)
Marriage is something that is sacred and contains the value of worship, in line with the greatness and how high the value of marriage is, in the hadith it is stated;